E-learning and the digital library - McDonald, Andrew (Henry Stewart Talks, 2012)
Defining e-learning, The role and benefits of e-learning, A new culture of learning, How good is e-learning?, Some drivers for change, The future of e-learning and next-generation learning technologies, The role of library managers and digital services, Strategic leadership and managerial influence, Linking with the learning environment, Developing learner-centred digital services and learning assets, Sophisticated automated systems and open source environments, Information literacy and workforce development, Future challenges